The Communist manifesto - Marx, Karl, 1818-1883; Engels, Friedrich, 1820-1895; Isaac, Jeffrey C., 1957-; Lukes, Steven (New Haven : Yale University Press, 2012)
Contains the "Communist Manifesto," several essays discussing the historical background of the manifesto and its influence today, all of the prefaces to the manifesto used during Marx and Engels' lifetime, and Engels' "Principles of Communism."
Introduction: rethinking the Communist manifesto / by Jeffrey C. Isaac -- A note on the texts -- Preliminary drafts of the Communist manifesto -- The text of the Communist manifesto -- Essays: The morals of the manifesto / by Steven Lukes; The Communist manifesto: between past and present / by Stephen Eric Bronner; Reflections on the fate of Marxism in Eastern Europe: fulfillment or bastardization / by Vladimir Tismaneanu; Marxism and globalization: revisiting the political in the Communist manifesto / by Saskia Sassen.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Marx, Karl, -- 1818-1883.; Manifest der Kommunistischen Partei (Marx, Karl); Communism; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; PHILOSOPHY -- Political; Communism; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.